Determinan Financial Distress: Profitabilitas, Modal Intelektual, dan Akuntabilitas pada Perusahaan Makanan - Minuman di Bursa Efek Indonesia (Jurnal Akuntansi dan Manajemen STIE Karya, 2026)
This study aims to examine the influence of profitability, intellectual capital, and accountability on the risk of Financial Distress among food and beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach with an associative design. Using purposive samapling, 10 companies were selected, yielding 50 obser-vations. Secondary data were obtained from annual reports and financial statements. Financial Distress risk is proxied by the Altman Z-score, profitability by Return on Assets (ROA), intellec-tual capital by the Value Added Intellectual Coefficient (VAIC™), and accountability by an accountability disclosure index. Data were analyzed using descriptive statistics, classical assump-tion tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination, with the aid of SPSS software. The results indicate that profitability has a positive effect on the Altman Z-score, whereas intellectual capital has no effect on the Z-score. Accountability has a negative effect on the Z-score. Simultaneously, the three independent variables influence the Z-score. The model yields an Adjusted R-Square value of 25.6%, indicating that the majority of the variation in Financial Distress risk is explained by factors outside the model.